Efektivitas Model Project Based Learning dalam Kemampuan Berpikir Kreatif Siswa (Studi Kasus Siswa Kelas XI AKL SMK Negeri 1 Jember Mata Pelajaran Project Kreatif dan Kewirausahaan) - Diah Niken Wulandari (Fakultas Ekonomi dan Bisnis, 2025)
This research aims to determine the effectiveness of the project based learning model on the creative thinking abilities of class XI AKL (Financial and Institutional Accounting) students at SMKN 1 Jember. The type of research used is a pre experimental design with a one group pretest-posttest pattern. Sampling was taken using purposive sampling for class XI AKL 2 students. Data collection techniques used observation, interviews and documents. The data analysis technique for hypothesis testing uses Paired Sample T-Test. The results of the research show that the project based learning model is effectively used on students' creative thinking abilities because there is an increase in students' creative thinking abilities with the percentage of each indicator increasing, initially from 57% of students' initial creative thinking abilities in the good category to 84% of students' final creative thinking abilities in the very good category. The application of a project learning model based on creative thinking skills can improve students' ability to find ideas, express student opinions and the ability to think fluently to develop unique products that will be planned.
Reaploud Repository February 2026_Hasyim
Keywords: Effectiveness; Project Based learning model; and Creative Thinking Ability